2021
DOI: 10.30574/gscarr.2021.6.3.0049
|View full text |Cite
|
Sign up to set email alerts
|

Allium sativum, a potential phytopharmacological source of natural medicine for better health

Abstract: Allium sativum, is a perennial flowering bulb which has been consumed worldwide as a functional food and known from thousands of years for its medicinal and culinary properties. Therapeutic potential of garlic is attributed to presence of its vital phytoconstituents. In present review, a complete therapeutic profile of drug is summarized by discussing its potential benefits highlighting the bioactive constituents. Phytoconstituents of crude drugs are used as antiviral, antioxidant, anti-inflammatory, antibacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…In the last decades, the popularity of organosulfur compounds present in the extract of garlic has increased tremendously (Hart et al, 2010). It is documented in many studies that A. sativum and its organosulfur constituents have the characteristics of antioxidants, antibacterial, anti-inflammatory, immuno-modulatory, antifungal, as well as protective properties for the cardiovascular and digestive systems including hepatoprotection, anticancer, antidiabetic, anti-obesity, renal and neuroprotective properties (Gudalwar et al, 2021). Garlic as a good source of sulfur-containing bioactive compounds can be used in the formulation of food and nutraceutical products for the control and prevention of various diseases (Mikaili et al, 2013).…”
Section: Chemical Composition Of Garlicmentioning
confidence: 99%
“…In the last decades, the popularity of organosulfur compounds present in the extract of garlic has increased tremendously (Hart et al, 2010). It is documented in many studies that A. sativum and its organosulfur constituents have the characteristics of antioxidants, antibacterial, anti-inflammatory, immuno-modulatory, antifungal, as well as protective properties for the cardiovascular and digestive systems including hepatoprotection, anticancer, antidiabetic, anti-obesity, renal and neuroprotective properties (Gudalwar et al, 2021). Garlic as a good source of sulfur-containing bioactive compounds can be used in the formulation of food and nutraceutical products for the control and prevention of various diseases (Mikaili et al, 2013).…”
Section: Chemical Composition Of Garlicmentioning
confidence: 99%
“…Garlic contains enzymes, minerals, and vitamins ( Shang et al, 2019 ). Bioactive compounds in garlic have shown antioxidant, anticancer, antidiabetic, neuroprotective, and hepatoprotective effects on the cardiovascular, renal, and digestive systems ( Gudalwar et al, 2021 ; El et al, 2021 ).…”
Section: Background Informationmentioning
confidence: 99%
“…In other research, garlic has shown the ability to reduce nitric oxide (NO) and prostaglandin E2 (PGE2) production by decreasing the expression of inducible NO synthase [iNOS] and cyclooxygenase-2 [COX2] ( 19 ). Various diseases will cause tissue injury; they are related to inflammation reactions.…”
Section: Introductionmentioning
confidence: 99%